Alih Kode Dan Campur Kode Dalam Video Youtube Xaviera Putri Kajian : Sosiolinguistik - Riawati Riawati; Emawati Emawati (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study aims to discuss and identify forms of code switching and code mixing, analyze the causal factors, and observe the dominance of these forms in Xaviera Putri's YouTube videos. The study was conducted using a qualitative descriptive approach with listening and note-taking techniques, with content analysis of 37 speech data from monologue videos. The results showed that code mixing was the most dominant form, with 24 data, compared to code switching with 13 data. The most common causal factors were bilingualism habits and conversation topics. This phenomenon reflects the communication style of the younger generation in the digital era, which is flexible, expressive, and reflects a multilingual identity. This finding is in line with the sociolinguistic theory of Suwito, Holmes, and Wardhaugh, which emphasizes the close relationship between language choice, social context, and identity strategies.